Pengaruh Likuiditas dan Perputaran Kredit Terhadap Rentabilitas Ekonomi di Bank Perkreditan Rakyat Artha Mitra Kencana - Nastiti Rizky Shiyammurti; Juniaman Waruwu (Jurnal Mutiara Ilmu Akuntansi, 2024)
Profitability is the ability of a company to generate profits in a certain period based on sales, investment, capital and asset. This study aims to determine the effect of liquidity and credit turnover on profitability partially and simulataneously at PT. BPT Artha Mitra Kencana in 2014-2023. The type of research used is quantitative research, with the sampling technique using saturated sampling. The research method used in this research is descriptive and associative method with the help of the SPSS 25 application. The results of this study indicate that partially the liquidity variable has a positive and significant effect on profitability, and credit turnover has a positive and significant effect on profitability. But simulataneously the variable of liquidity and credit circulation have a significant effect on profitability.